تنمية مهارات التواصل الشفوي في ضوء مناهج الجيل الثاني- الطور الأول من التعليم الابتدائي أنموذجا-developing Oral Communication Skills In Light Of The Second Generation Curricula- The First Phase Of Primary Education As A Model – - أبركان نوال; شتوح زهور (université msila, 2022)
يهدف تعليم اللغة العربية بداية بالمرحلة الابتدائية إلى اكساب المتعلم مادة التواصل اليومي، وتعزيز رصيده اللغوي من خلال تنمية مهاراته اللغوية التواصلية؛ ويتجلى ذلك في النطق الصحيح، والأداء الحسن، والتعبير الجيد، وقد بنيت مناهج اللغة العربية من خلال إصلاحات مناهج الجيل الثاني في التعليم الابتدائي على هذا الأساس؛ حيث أصبح تعليم اللغة العربية يقوم على الميادين الأربعة الآتية: ميدان فهم المنطوق، ميدان التعبير الشفوي، ميدان فهم المكتوب، وميدان التعبير الكتابي، وتسعى مناهج اللغة العربية من خلال ميدان فهم المنطوق وميدان التعبير الشفوي إلى تنمية مهارتي الاستماع والتحدث لدى المتعلم، كأساس يبنى عليه الفهم؛ الذي يمثل مفتاح النفاذ إلى كل التعلمات، وقاعدة لبناء كفاءة التواصل. Teaching Arabic, beginning at the primary stage, aims to provide the learner with the material of daily communication, and to enhance his linguistic balance by developing his communicative language skills; This is reflected in the correct pronunciation, good performance, and good expression; The Arabic language curricula were built through the reforms of the second generation curricula in primary education on this basis. As the teaching of the Arabic language has become based on the following four fields: the field of spoken understanding, the field of oral expression, the field of understanding the written, and the field of written expression. The Arabic language curricula seek through the field of spoken understanding and the field of oral expression to develop the learner's listening and speaking skills, as a basis upon which understanding is built; which represents the key to accessing all learning, and the basis for building efficient communication
Keywords:  مهارات التواصل الشفوي ;  مناهج الجيل الثاني ;  التعليم الابتدائي ;  oral communication efficiency ;  second generation curricula ;  primary education